FORMULASI FILM FORMING SPRAY DARI KLORAMFENIKOL UNTUK LUKA - Rusdiati Helmidanora; Siti Jubaidah; Is alukal Fauziah A.A (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The wound healing process should be short so as not to interfere with productivity and reduce costs. SFFS (spray film forming system) is a combination of transdermal preparations in which a polymer solution is sprayed onto the skin and will form an almost transparent film by evaporation of the solvent. Film-forming solutions are particularly advantageous for transporting the active substance to the site of action by the shortest route in cases of dermal or lower tissue infections. Chloramphenicol is a lipophilic drug so it penetrates the skin well because the stratum corneum matrix is ​​also lipophilic. The purpose of this study was to make a formulation of a sprayed chloramphenicol film-forming solution in order to obtain the best formula and increase effectiveness. The research was carried out on an experimental basis and three formulas were prepared with different polymer concentrations. The results of the study obtained a film-forming spray for each formula with a film formed that was flexible and adhered well to the skin, with a pH of 6. The time needed to make the film layer in skin is 0.87-1.19 minutes with an average dose weight of spray is 61.33-85.33 mg.